Home free - Michaels, Fern. (New York : Kensington Pub. Corp., 2011)
The vigilantes of the Sisterhood reorganize as a secret group called the CIC and dedicated to serving their friend, the president of the United States, Martine Connor.
Includes a special preview of Southern comfort (p. [335]- 362).
Keywords: Female friendship -- Fiction; Vigilantes -- Fiction; Undercover operations -- Fiction; Search and rescue operations -- Fiction; Hostages -- Fiction; Rescue work -- Fiction; Women presidents -- United States -- Fiction